2006
DOI: 10.1128/aem.72.1.178-184.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inhibition of Acetoclastic Methanogenesis on Growth of Archaeal Populations in an Anoxic Model Environment

Abstract: Methyl fluoride is frequently used to specifically inhibit acetoclastic methanogenesis, thus allowing determination of the relative contribution of acetate versus H 2 /CO 2 to total CH 4 production in natural environments. However, the effect of the inhibitor on growth of the target archaeal population has not yet been studied. Therefore, we incubated rice roots as an environmental model system under anoxic conditions in the presence and absence of CH 3 F, measured the activity and Gibbs free energy (⌬G) of CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 49 publications
4
33
0
Order By: Relevance
“…respectively. It is suggested that the T-RFs of 185 bp represents members of Methanosarcinaceae or RC-VI (Kemnitz et al 2004), 382 bp members of the euryarchaeal RC-III, and the T-RF of 394 bp members of the methanogenic RC-I, (Kemnitz et al, 2004;Penning and Conrad, 2006). This affiliation is consistent with the clone library: archaeal 16S rRNA gene clone sequences from the original soil belonged exclusively to RC-VI (Fig.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…respectively. It is suggested that the T-RFs of 185 bp represents members of Methanosarcinaceae or RC-VI (Kemnitz et al 2004), 382 bp members of the euryarchaeal RC-III, and the T-RF of 394 bp members of the methanogenic RC-I, (Kemnitz et al, 2004;Penning and Conrad, 2006). This affiliation is consistent with the clone library: archaeal 16S rRNA gene clone sequences from the original soil belonged exclusively to RC-VI (Fig.…”
Section: Resultssupporting
confidence: 72%
“…The tubes were closed with butyl rubber stoppers and flushed with N 2 . In inhibition experiments, CH 3 F, a specific inhibitor of acetoclastic methanogenesis, was added to the gas phase to a final concentration of 1% (Frenzel and Bosse 1996;Penning and Conrad 2006).…”
Section: Experimental Designmentioning
confidence: 99%
“…Vercelli soil contains a wide diversity of methanogenic archaea, including acetoclastic Methanosarcinaceae and Methanosaetaceae as well as hydrogenotrophic Methanocellales, Methanomicrobiales, and Methanobacteriales (11,20). CH 4 is formed by both pathways in Vercelli soil (50), but on rice roots, CH 4 is formed mostly by the reduction of CO 2 (51). Furthermore, Lu and Conrad (18) showed that in particular Methanocellales incorporate rice plant carbon in the rhizosphere, but Methanosaetaceae and Methanomicrobiaceae are also active (52).…”
Section: Discussionmentioning
confidence: 99%
“…Later, we corrected this value to −12 to −15 kJ per mol reaction, based on new insights into the stoichiometry of the ATPase reactions and considerations on the energy charge of syntrophically fermenting bacteria (Schink and Stams 2013). Energy gains in this range were reported before for syntrophic oxidation of butyrate (Adams et al 2006;Wang et al 2013), propionate (Krylova and Conrad 1998;Scholten and Conrad 2000), and acetate (Hao et al 2010;Schnürer et al 1997), as well as for homoacetogenic fermentation (Conrad and Wetter 1990;Fey and Conrad 2000;Seitz et al 1990), aceticlastic methanogenesis (Fey and Conrad 2000;Penning and Conrad 2006), and hydrogen-dependent methanogenesis (Dwyer et al 1988;Seitz (Müller 2015;Spahn et al 2015, Lim et al 2014. In any case, we have to keep in mind that measurements of bulk concentrations both in the gas phase and in the liquid phase give only a rough estimate of the actual in situ concentrations of the intermediates within the microstructure of microbial aggregates (Pauss et al 1990).…”
Section: Discussionmentioning
confidence: 99%